2007
DOI: 10.5488/cmp.10.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Coupling parameter for low-temperature plasma with condensed phase

Abstract: The conditions of formation of ordered structures in low-temperature plasma with the condensed disperse phase are studied. Various modifications of the coupling parameter for polydisperse systems of condensed grains are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this connection, a number of works have been devoted to agglomeration processes, electroacoustic properties and self-ordering processes of a heterogeneous system [5][6][7]. It is shown, that among the combustion products the significant fraction is the agglomerates which consist of particles with dimensions about ten nanometers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, a number of works have been devoted to agglomeration processes, electroacoustic properties and self-ordering processes of a heterogeneous system [5][6][7]. It is shown, that among the combustion products the significant fraction is the agglomerates which consist of particles with dimensions about ten nanometers.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that the condensed phase of combustion products includes both single nanosized metal oxide grains and larger components consisting of nanoparticle agglomerates [5][6][7]. Agglomerates contain a sufficiently large number of pores of different shapes and sizes, so they can be used as sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that for a three-dimensional grating and monochromatic incident ray (for example, a laser beam) there is only one diffracted ray 4 (see Fig. 1), and it lies in the same plane with the incident 1 and transmitted 3 rays, and its «exit angle» from the grating is equal to the angle of the incident ray Θ [15]. When monochromatic rays with different directions enter the volumetric grating, only that diffracted ray will be observed, the propagation direction of which satisfies the Wulff-Bragg's equation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it follows from [15] that the intensity of the diffracted ray I is proportional to the square of the number of those elements of the grating N that are within the volume V of the intersection of the incident laser beam with the diffraction grating, i.e. I ~ N 2 .…”
Section: Introductionmentioning
confidence: 99%